KURIKULUM CINTA DALAM PERSPEKTIF PENDIDIKAN HUMANIS: ANALISIS KOMPARATIF PEMIKIRAN HAMKA DAN PAULO FREIRE - Nur Febriana, Finta; Nadzifah Aisyah Fauzi; Syahrul Ardiansyah; Muhammad Nur Ikhsanudin; Nur Laila Ana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This article examines the concept of the “curriculum of love” as a pedagogical paradigm that integrates spiritual and humanistic dimensions in Islamic education through a comparative approach to the thoughts of Haji Abdul Malik Karim Amrullah (Hamka) and Paulo Freire. Hamka views education as a process of developing human nature (fitrah) through moral formation, spiritual strengthening, and the attainment of balance between worldly and hereafter life based on the values of tawhid and modern Sufism, while Freire positions education as a process of humanization and liberation through the development of critical consciousness built upon dialogue and pedagogical relationships grounded in love for humanity. Although emerging from different intellectual traditions, both thinkers share common ground in viewing education as a transformative process aimed at fully humanizing human beings. This study employs a qualitative approach using library research and comparative-hermeneutic analysis through the examination of the major works of both figures and relevant supporting literature. The findings reveal that the synthesis of Hamka’s and Freire’s thoughts produces a conceptual framework of the “curriculum of love” consisting of five main dimensions: tawhid as a spiritual foundation, dialogue as a pedagogical approach, liberation as the orientation of education, morality (akhlak) as a humanistic goal, and learning communities as spaces of social praxis. This concept offers an alternative to educational paradigms that tend to focus merely on cognitive and administrative aspects and is relevant in addressing the challenges of educational secularization, dehumanization caused by technological development, and the moral crisis in contemporary Islamic education.